1999
DOI: 10.1002/(sici)1097-4628(19990531)72:9<1139::aid-app4>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Revisit the crystallization mechanism of vectra,? a liquid crystal polymer

Abstract: ABSTRACT:We have studied isothermal transition kinetics and crystallization mechanisms of the Hoechst Celanese liquid crystal polymer Vectra™ A-950 using a differential scanning calorimetry. This material is a random copolymer with a composition made of 73 mol %/27 mol % of HBA (1,4-dihydroxybenzoic acid)/HNA (2,6-dihydroxynaphthoic acid). When comparing our results to previous work on 75/25 HBA/ HNA, we found some similarities as well as dissimilarities. In the case of similarities, both polymers show two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…The thermal treatment also produces a second endotherm for B-N and RD1000. Previously, Chung et al and Romo-Uribe et al had reported the production of a second endotherm in B-N [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal treatment also produces a second endotherm for B-N and RD1000. Previously, Chung et al and Romo-Uribe et al had reported the production of a second endotherm in B-N [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the characteristic high‐melting temperature, LC polyesters are often melt processable with enhanced shear thinning, resulting from anisotropy that reduces the viscosity of the melt at typical processing temperatures . This feature renders LC polyesters excellent candidates for a variety of commercial applications, including but not limited to protective coatings, displays, electronic devices, composites, substrates, and flame‐resistant structures …”
Section: Introductionmentioning
confidence: 99%
“…Manipulating the orientation of the anisotropic macromolecules optimizes mechanical properties of LCP fibers . Molecular alignment and microstructure are controlled through processing conditions during fiber spinning and heat treatment . At the molecular level, the degree of straightness in the molecular architecture of the polymers studied here (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The double aromatic ring in the N monomer acts as a parallel offset thereby disturbing the regularity of molecular packing, thus lowering the solid‐to‐nematic transition temperature . Despite the evident importance and striking physical properties of commercial thermotropic LCPs, there are to date few studies addressing the influence of thermal treatment on their mechanical properties …”
Section: Introductionmentioning
confidence: 99%